Corona delta varian news text: critical discourse analysis on TV talkshows’ head line - Tampubolon, Sahlan; Sipayung, Kammer; Napitupulu, Fenty Debora; Sidabutar, Usman (Linguistics and Culture Review, 2021)
Objectives: This study is about the realization of critical discourse analysis on TV talkshows’ headlines about corona delta variant. Methods: The data was gathered by collecting 31 headline news stories about Corona from three TV channels: Metro TV, TV One, and Kompas TV. Result: The result showed that at the level of micro, the linguistic features used by the three TV channels were dominated by expressing declarative ideas. On the level of macro, the three TV channels used facts as information and statements as information. On the level of meso, it was discovered that the three TV channels used their roles as public behavior influencers, information providers, policy evaluators, and socialization agencies. The conclusion: the ideology of the TV channel influences the way of delivering news CDA, coronavirus delta variant news, TV talk shows.